Files - Marcella, Albert J., Jr; Guillossou, Frederic (Cyber Forensics, 2012)
This chapter examines hexadecimal (HEX) and discusses the relevance of HEX when examining file signature metadata. It is noted that some data contains within a file cannot be viewed in a legible or searchable text format such as ASCII or Unicode, specifically data contain within file headers, such as the file signature, thus there is necessity of a working knowledge of HEX. It is important to understand that not all binary values are convertible into readable ASCII. ASCII is a code, based on the ordering of the English alphabet¸ and not all data contained within a computer is necessarily text (ASCII) based. There are many programs or software applications which are written in programming code which is not ASCII based.